Greening the covenant : integrating environmental considerations in the Interpretation of States Parties' Obligations under Article 2(1) of the International Covenant on Economic Social and Cultural Rights - Donald, Megan Elizabeth (Stellenbosch : Stellenbosch University, 2021)
Thesis (LLD)--Stellenbosch University, 2021.